Infections Caused by Mycobacterium tuberculosis in Recipients of Hematopoietic Stem Cell Transplantation - Al-Anazi, Khalid Ahmed; Al-Jasser, Asma Marzouq; Alsaleh, Khalid (Frontiers in Oncology, 2014)
Mycobacterium tuberculosis (M. tuberculosis) infections are uncommon in recipients of hematopoietic stem cell transplantation. These infections are 10 to 40 times commoner in recipients of stem cell transplantation than in the general population but they are 10 times less in stem cell transplantation recipients compared to solid organ transplant recipients. The incidence of M. tuberculosis infections in recipients of allogeneic stem cell transplantation ranges between ˂ 1% and 15% and varies considerably according to the type of transplant and the geographical location. Approximately 80% of M. tuberculosis infections in stem cell transplant recipients have been reported in patients receiving allografts. Several risk factors predispose to M. tuberculosis infections in recipients of hematopoietic stem cell transplantation and these are related to the underlying medical condition and its treatment, the pre-transplant conditioning therapies in addition to the transplant procedure and its own complications. These infections can develop as early as day 11 and as late as day 3337 post-transplant. The course may become rapidly progressive and the patient may develop life-threatening complications. The diagnosis of M. tuberculosis infections in stem cell transplant recipients is usually made on clinical grounds, cultures obtained from clinical specimens, tissues biopsies in addition to serology and molecular tests. Unfortunately, a definitive diagnosis of M. tuberculosis infections in these patients may occasionally be difficult to be established. However, M. tuberculosis infections in transplant recipients usually respond well to treatment with anti-tuberculosis agents, provided the diagnosis is made early. A high index of suspicion should be maintained in recipients of stem cell transplantation living in endemic areas and presenting with compatible clinical and radiological manifestations. High mortality rates are associated with infections caused by multidrug resist